Effect of CO2 on coal devolatilization in oxy-fuel combustion: Exploring the influence of temperature and inherent alkali/alkaline earth metal. (May 2020) - Du, Yongbo; Zhao, Nan; Wang, Junxiong; Zhang, Jinping; Wang, Chang'an; Che, Defu
Highlights: Char property was compared between prepared in N2 and CO2 . CO2 -char has much larger specific surface area but lower reactivity. The differences increases with temperature or Ca content in coal. Char morphology difference was observed only for high-Ca coal. Abstract: Oxy-fuel combustion needs recycled flue gas to reduce furnace temperature for material protection. The enhanced CO2 alters coal devolatilization behavior. Devolatilization (albeit very quick) determines the whole life of coal in furnace, and thus it is essential to clarify the effects of CO2 gas media on coal devolatilization behavior. However, previous works achieved conflicting results due to operation condition and coal nature differences. The present work attempts to investigate this issue and explore the influence of devolatilization temperature and alkali/alkaline earth metal. For this purpose, five coals with three coal ranks and different mineral compositions were devolatilized within N2 or CO2 by using a drop tube furnace under 800−1200 °C. Char produced in CO2 has much more mesopores and as much as 2.8–8.1 times (depending on coal type) specific surface area than char produced in N2, but the combustion reactivity is slightly lower. These differences are due to the additional CO2 gasification contribution. With increasing devolatilization temperature or inherent Ca content, the impact of CO2 on devolatilization behavior is more pronounced. Difference in char surface morphology was observed only for high-Ca coal.